Determination of Free Fatty Acid in Frying Oils of Various Foodstuffs - F. Febrianto; A. Setianingsih; A. Riyani (Universitas Negeri Yogyakarta, 2020)
Cooking oil is one of the basic human needs as food processing media. Repeated use of cooking oil by heating at high temperature will produce free fatty acid levels. This study aim to determine the levels of free fatty acids in frying oils of various foodstuffs which were chicken, catfish, and flour with acid base titration method. The study population was frying oils of various foodstuffs of 0 up to 5th. The results of fatty acid levels in the repeated use of chiken (sample A), catfish (sample B) and flour foodstuffs shows the fatty acid levels exceed safe limits set by SNI 7709:2012. The fatty acid levels of the oil before it used was 0.24%. The increase of free fatty acid was influeced by how many the coocing oil used to frying. The highest level of fatty acid in coocing oil was reached after the fifth of friying. It happened because the level water in foodstuffs increase due to the used of coocing oil